2010
DOI: 10.4028/www.scientific.net/msf.636-637.772
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultraviolet Absorbers (UVA) and Hindered Amine Light Stabilizers (HALS) in ABS Stabilization

Abstract: The present work evaluates the combination effect of hindered amine light stabilizers (HALS) and ultraviolet absorbers (UVA) on the ultraviolet (UV) stability of acrylonitrile-butadiene-styrene (ABS). Thus, two types of light stabilizers, Tinuvin P and Chimassorb 119 FL, were used to improve the ABS endurance against UV. Stabilized ABS samples were submitted to accelerated weathering in a Xenontest 150 S chamber, according to standard methods, in order to predict copolymer lifetime within a commercially accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The strongest effect was noticed with the WoM‐treatment; after 600 h in the test chamber, the b*‐ value had increased about 40%. This is in agreement with the results reported by Santos et al [20] who observed an increase in the yellowness index after exposure to UV‐ light.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The strongest effect was noticed with the WoM‐treatment; after 600 h in the test chamber, the b*‐ value had increased about 40%. This is in agreement with the results reported by Santos et al [20] who observed an increase in the yellowness index after exposure to UV‐ light.…”
Section: Resultssupporting
confidence: 93%
“…FTIR is an important tool for characterizing degradation of polymers and consequently it has been applied to ABS in several studies [2, 3, 20, 24]. Here only changes induced by the ageing to the absorption bands corresponding to carbonyl groups (1600–1800 cm −1 ), 1,4 butadiene (966 cm −1 ) and 1,2 butadiene (911 cm −1 ) will be discussed.…”
Section: Resultsmentioning
confidence: 99%
“…74, 75 Blending light stabilizers (UV absorbers with HALS) to obtain synergistic effects is of considerable research interest. 76 Polyesterpolyurethane clear-coat formulations that contained both HALS and UV absorbers, for instance, show a synergistic light-stabilizing effect. However, this is not a general observation.…”
Section: Approaches To Uv-stabilization Of Materialsmentioning
confidence: 99%